Posledice ukrepov za zajezitev epidemije covida-19 na gibalni razvoj otrok - Lebar, Aleš (Šport (Ljubljana), 2023)
The article presents the trends in motor development of girls and boys from Janka Modra Primary School after the introduction of covid-19 mittigation measures. We included the SLOfit-Sports Educational Chart measurements of the pre-corona generations who attended the fourth grade in the school years 2015/16, 2016/18, 2017/18 and 2018/19, and the two corona generations of fourth-graders from the school years 2020/21 and 2021/22. The comparison was made in three groups according to body fat, and it showed that in all three groups children of both corona generations experienced the most unfavorable development. At the same time, the trends in the generation of fourth-graders from the 2021/22 school year were positive, but they still remained well below the average of their peers from the period before the epidemic. There was a decline in most motor abilities, but it was most pronounced in coordination and speed of alternating moves.
Keywords: COVID-19; četrtošolci; gibalne sposobnosti; SLOfit; šport; športna vzgoja; trend